A test of their linkage between money supply, liquidity, and share prices - Chung, Tin Fah (2013)
This thesis reports new evidence of a liquidity effect from money supply changes. From evidence, the money supply increases proposed by Friedman (1969) first lead to interest rate declines and inflation increases. Yet the proposition that money supply increase leads to liquidity surge and credit expansion in the banking sector – has not yet received unanimous empirical support. Monetary transmission mechanism is more and more turning to the credit channel to trace how money affects prices. That money is endogenously determined as in the writings of post-Keynesian (PK) economists, will be examined in this thesis by applying a 3-equations model. The empirical tests of the theories are conducted using quarterly data over 1960 and 2011 for the G-7 countries: Canada, France, Germany,Italy, Japan, the United Kingdom (UK) and the United States (US). These tests are conducted to determine whether (1) money is endogenous (bidirectional) or exogenous (unidirectional), (2) money supply causes liquidity, and (3) liquidity causes share price to change. The empirical tests are conducted after the usual statistical tests (unit root,Granger causality, Johansen cointegration tests and VECM) are done on whether the data are stationary and cointegrated. The results reported in this thesis are: i) bidirectional causality exists between GDP and money supply suggesting that money is endogenous; ii) there is a difference between long-term and short-term causality – as in the cases of Canada, Italy, Japan and the US. In contrast, France’s and Germany’s monetary policies appear to be in accordance with the monetarist view; iii) liquidity is found to be a significant variable in most cases except Canada 2 (in sub-period 1991:1 to 2007:1) and Italy; and iv) for most G-7 countries, there is a relationship between money supply and share returns. Finally, the findings using the panel data estimation method show that there is a positive relationship between money supply growth and share returns: it is negative between share returns and money supply growth, due to central bank changing interest rates to curb inflation. In this context, there is a bidirectional positive relation between GDP growth and money supply growth, which supports the PK theory of endogenous money. Thus, the money-to-share-price-returns relation is founded on money being endogenous. The findings of the thesis provides a link between money supply,liquidity and the real economy, unlike the more narrower-focused asset pricing theories that purport to explain asset prices as determined by just the financial factors.